Gestural coupling and social cognition: Möbius Syndrome as a case study - Krueger, Joel; Michael, John (Frontiers in Human Neuroscience, 2012)
Social cognition researchers have become increasingly interested in the ways that behavioral, physiological and neural coupling facilitate social interaction and interpersonal understanding. Some researchers endorse strong interactionism (SI), which conceptualizes low-level coupling processes as alternatives to higher-level individual cognitive processes; the former at least sometimes render the latter superfluous. In contrast, we espouse moderate interactionism (MI), which is an integrative approach. Its guiding assumption is that higher-level cognitive processes are likely to have been shaped by the need to coordinate, modulate and extract information from low-level coupling processes. In this paper, we present a case study on Möbius Syndrome (MS) in order to contrast SI and MI. We attempt to show how MS—a rare form of congenital bilateral facial paralysis—can be a fruitful source of insight for research exploring the relation between high-level cognition and low-level coupling. Lacking a capacity for facial expression, individuals with MS are deprived of a primary channel for gestural coupling. According to SI, they lack an essential enabling feature for social interaction and interpersonal understanding more generally and thus ought to exhibit severe deficits in these areas. We challenge SI’s prediction and show how MS cases offer compelling reasons for instead adopting MI’s pluralistic model of social interaction and interpersonal understanding. We conclude that investigations of coupling processes within social interaction should inform rather than marginalize or eliminate investigation of higher-level individual cognition.